Intrusion prevention within a SDN environment - Davies, J.N.; Comerford, P.; Verovko, M.V.; Skiter, I.S.; Posadska, I.S. (Математичні машини і системи, 2017)
Recent investigations have highlighted the complexity and interrelationship between components of the infrastructure of the internet. In an attempt to simplify the management of the infrastructure a great deal of research has taken place in the area of Software Defined Networks (SDN). This paper investigates the perceived developments in the network infrastructure and how they can be accommodated with a SDN environment. In particular the deployment of Intrusion prevention, a well-known function found in most computer networks, is investigated. A hardware design is offered as a solution and it is shown how this can be integrated into a SDN.